Diversity of Microfungi in Sandy Beach Soil of Teluk Aling, Pulau Pinang - Latiffah Zakaria,; Teh Li Yee,; Maziah Zakaria ,; Baharuddin Salleh, (Tropical Life Sciences Research, 2011)
A total of 82 isolates of microfungi were isolated from 6 sandy soil samples collected from Teluk Aling beach, Pulau Pinang. The soil microfungi were isolated by using direct isolation, debris isolation and soil dilution techniques. Based on morphological characteristics, seven genera of microfungi were identified namely, Fusarium (42%), Aspergillus (24%), Trichoderma (13%), Curvularia (9%), Colletotrichum (6%), Helminthosporium (4%) and Penicillium (2%). The most common species isolated was Fusarium solani followed by Fusarium semitecum, Aspergillus niger, Trichoderma viride, Curvularia clavata, Curvularia lunata, Helminthosporium velutinum, Colletotrichum sp. and Penicillium chrysogenum. From the present study, it appears that the sandy beach contains a microfungi reservoir comprising of a variety of genera which contributes significantly to the ecological functioning of a marine ecosystem. Sejumlah 82 pencilan mikrokulat telah dipencilkan daripada 6 sampel tanah pantai yang dikutip dari pantai Teluk Aling, Pulau Pinang. Mikrokulat daripada tanah tersebut dipencilkan melalui kaedah pemencilan terus, pemencilan piung dan teknik pencairan. Berdasarkan pencirian secara morfologi, tujuh genera mikrokulat telah dikenalpasti iaitu Fusarium (42%), Aspergillus (24%), Trichoderma (13%), Curvularia (9%), Colletotrichum (6%), Helminthosporium (4%) and Penicillium (2%). Spesies yang paling kerap dipencilkan adalah Fusarium solani diikuti dengan Fusarium semitecum, Aspergillus niger, Trichoderma viride, Curvularia clavata, Curvularia lunata, Helmintosporium velutinum, Colletotrichum sp. dan Penicillium chrysogenum. Daripada kajian yang dilakukan, didapati pantai berpasir mengandungi takungan pelbagai genera mikrokulat yang memberikan sumbangan yang signifikan terhadap fungsi ekologi ekosistem marin.